EFEKTIVITAS MODEL PROBLEM BASED LEARNING DAN INQUIRY LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR IPAS SD - Pohan, Talita BR; Endang Indarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aimed to prove the effectiveness of the Problem Based Learning (PBL) and Inquiry Learning models in improving critical thinking skills and learning outcomes in Science and Social Studies (IPAS) among elementary school students. The research design used was experimental with a Nonequivalent Control Group Design. This design involved two classes, namely the experimental group and the control group. The study was conducted within the Hasanuddin Cluster of Elementary Schools in Salatiga City, Central Java Province. Data were collected through knowledge tests with a pretest conducted before and a posttest conducted after the learning sessions. The results showed a significant difference in the effectiveness of the two learning models on improving critical thinking skills and IPAS learning outcomes. The average learning outcome of the experimental group using PBL was 84.00, higher than the control group using IL with an average of 78.00. Based on the T-test results, there was a significant coefficient of 0.019, which was less than 0.05, thus Ho was rejected and Ha was accepted. This indicated that the PBL model was more effective in enhancing students' critical thinking skills and learning outcomes compared to the IL model. The study concluded that the implementation of the PBL model could provide a significant improvement in critical thinking skills and IPAS learning outcomes for fourth-grade elementary students.